2007
DOI: 10.4070/kcj.2007.37.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Restenosis after Drug-Eluting Stent Implantation

Abstract: Background and Objectives:Despite the dramatic reduction in restenosis conferred by drug-eluting stents (DES), restenosis remains a significant problem for real-world patients. Restenosis is a complex phenomenon, and a variety of stent-, drug-, patient-and lesion-related factors have been studied as the determinants of restenosis after DES implantation. Methods and Results:The stent delivery system, the polymer and the drug are integral components of DES, and these are the device-specific factors that can affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…In this study, the effect of the history of diabetes was significant on restenosis; it is similar to many previously conducted studies (19)(20)(21). However, some studies argued that the effect of diabetes was not significant on restenosis (22,23). The observed difference in the results can be attributed to the low prevalence of diabetes in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the effect of the history of diabetes was significant on restenosis; it is similar to many previously conducted studies (19)(20)(21). However, some studies argued that the effect of diabetes was not significant on restenosis (22,23). The observed difference in the results can be attributed to the low prevalence of diabetes in the present study.…”
Section: Discussionsupporting
confidence: 89%
“… 9) Additional risk factors for ISR include diabetes, lesion length, luminal cross-sectional area after stenting, the number and length of stents, and the plaque burden. 10 - 14) We found in a previous study that stent fracture may be another potential risk factor for ISR. 6) The patient reported here had diabetes, and stent under expansion was not observed after stent implantation.…”
Section: Discussionmentioning
confidence: 89%
“…The mechanism responsible for restenosis is associated with neointimal formation 9). Additional risk factors for ISR include diabetes, lesion length, luminal cross-sectional area after stenting, the number and length of stents, and the plaque burden 10-14). We found in a previous study that stent fracture may be another potential risk factor for ISR 6).…”
Section: Discussionmentioning
confidence: 96%
“…The complex, vexing problem of restenosis after balloon angioplasty is influenced by a variety of clinical and anatomic factors. Vessel size is an important anatomic factor, 17) and in fact, restenosis rate is inversely related to vessel diameter. 18) It has been reported that angiographic and clinical outcomes after balloon angioplasty and elective stent placement are best in vessels slightly smaller than 3 mm, 19) and regarding the treatment of stenotic coronary arteries with diameters below 3 mm, previous studies have demonstrated the superiority of implanting DES for restenosis reduction as compared to BMS implantation in SVD.…”
Section: Discussionmentioning
confidence: 99%